Augmentation of the Atrophic Mandible with a Block Corticomedullary Graft - Layla Louise de Amorim Rocha; Matheus Francisco Barros Rodrigues; Rodrigo da Franca Acioly; Daniel do Carmo Carvalho; Cristofe Coelho Lopes da Rocha (Hindawi Limited, 2020)
The gradual loss of the dental alveolus leads to bone resorption, which may cause atrophy of the maxilla and mandible. One of the most complex procedures in reconstructive surgery is the rehabilitation of patients with atrophic mandibles. Herein, we present a clinical case study of atrophic mandible augmentation with grafts obtained from the iliac crest. The use of reconstruction plates may represent a feasible mechanism for treatment as well as fracture prevention. Mandible augmentation performed by grafting the donor site of the iliac crest showed satisfactory results and resolution of the aesthetic and functional impairments.